An uncommon case of venomous snake bite complicated by intracranial haemorrhage - Parasher, Anant; Roy, Prabhat Gautam; Inamadar, Soumya (International Journal of Advances in Medicine, 2020)
Snake bite is a widespread and neglected public health problem in tropical and subtropical countries, where rural populations are mainly affected. Although venomous snake bite may lead to a wide range of complications, life-threatening neurological complications such as Intracerebral Haemorrhage (ICH) are rare and infrequently documented in literature. Here we discuss the case of a 64-year-old man who developed ICH following a viper bite, and the neurological sequelae that followed after management.